The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/maco.200603988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cerium addition on microstructure and corrosion resistance of die cast AZ91 magnesium alloy

Abstract: A novel AZ91 Ce containing magnesium alloy characterized by excellent corrosion resistance is fabricated by adding rare earth Ce (cerium) in the form of a Mg-Ce master alloy. The metallographic investigation shows that Ce added to AZ91 can obviously decrease the size of b-Mg 17 Al 12 and forms Al 11 Ce 3 intermetallic compounds in the shape of fine needles. The corrosion tests and electrochemical measurements indicate that the corrosion resistance of AZ91 Ce containing magnesium alloy is obviously higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…While this could be either the Al11Ce3 phase or (Al,Mg)2Ce phase, previous research has shown that Al11Ce3 phase has a needle-like structure [9] and is the more dominant phase compared to (Al,Mg)2Ce [10]. Furthermore, XRD results also suggests that more peaks were observed for Al11Ce3 phase.…”
Section: Phase Analysismentioning
confidence: 85%
“…While this could be either the Al11Ce3 phase or (Al,Mg)2Ce phase, previous research has shown that Al11Ce3 phase has a needle-like structure [9] and is the more dominant phase compared to (Al,Mg)2Ce [10]. Furthermore, XRD results also suggests that more peaks were observed for Al11Ce3 phase.…”
Section: Phase Analysismentioning
confidence: 85%
“…Previous investigations [8][9][10] have validated that ␤ phase distributed along ␣ grain boundary could act as a micro-galvanic cathode considering the potential difference between ␣ and ␤ phase. The micro-galvanic-current between ␤ phase and adjacent ␣ grain preferentially brings on the corrosion of ␣ grain, and the ␤ Fig.…”
Section: Discussionmentioning
confidence: 96%
“…phase was finally undermined and flaked away. However, the devastation of micro-galvanic-corrosion will be weakened if ␣ grain and ␤ phase are refined [10]. Moreover, solid solution of aluminum in ␣ phase is beneficial to the corrosion resistance of ␣ phase [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations